"If I had been given that information back then": An interpretive description exploring the information needs of adults with cerebral palsy looking back on their transition to adulthood. (11th June 2018) - Freeman, M.; Stewart, D.; Cunningham, C. E.; Gorter, J. W.
Abstract: Background: Young people with cerebral palsy (CP) and their families have identified lack of information received during the transition to adulthood as a barrier to successful outcomes. To date, few studies have explored the information needs, preferences, timing, and method of provision from the perspective of individuals with CP. Method: The methodological approach to this qualitative study was interpretive description. Nine adults living with CP, between the ages of 20 and 40, were purposively recruited in Ontario, Canada, to explore, retrospectively, their information needs during the transition to adulthood. Participants completed a 1‐hour interview that explored their experiences seeking and receiving information. Interviews were transcribed verbatim, and data were analysed to create a thematic description of adults' experiences with information. Results: Three themes emerged: (a) "Recognizing and supporting information needs, " which highlighted the importance of support systems to assist young people in receiving and seeking information throughout the transition; (b) "Getting creative, " which highlighted strategies young people use when confronted with environmental barriers when seeking information; and (c) "Gaps and advice for the future, " which highlighted the need for real‐life opportunities, during the transition to adulthood, to experience some of the responsibilities of adult life. Conclusion: Clinicians assisting young people with CP need purposefully to foster knowledge and skills during the transition to adulthood. They should be not only providers of information but also enablers of opportunities for immersion in real‐life experiences to prepare for adult life. It is important for young people to have the opportunity to discuss challenges and exchange information with their peers.